DETERMINATION OF THE CONCEPT OF VIRTUAL PERMANENT ESTABLISHMENT IN ELECTRONIC TRANSACTIONS TO CREATE LEGAL CERTAINTY - Emelia Retno Kadarukmi, Maria (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This article is intended to analyze the following issues, the establishment of the concept of virtual Permanent Establishment (BUT) and the criteria required to create legal certainty in the collection of income tax on transactions via the Internet. Based on the research results, it is known that essentially e-commerce transactions are not visible (intangible). Through the definition of Article 2 paragraph (5) letter p, the Government attempts to